MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL APTITUDE TREATMENT INTERACTION (ATI) SISWA KELAS X SMAN 3 MERANGIN - Yohanes (Pendidikan Matematika | Universitas Merangin, 2016)
Purpose of this study is to describe an increase in mathematics learning outcomes in the three dimensional space material using the Aptitude Treatment Interaction (ATI) Model in class X SMA N 3 Merangin Academic Year 2016/2017. This research is a classroom action research which consists of four stages, namely planning, action, observation and reflection carried out in SMA N 3 Merangin with the research subjects being all class XB SMA N 3 Merangin 2016/2017 Academic Year totaling 28 people. The study was conducted in two cycles, each cycle consisting of III meetings. Data was collected using observation and evaluation, observations in the form of student activity sheets, for evaluation of learning outcomes tests in the form of essay test questions. Data analysis techniques use simple statistics. The results of the study indicate that the Aptitude Treatment Interaction (ATI) Learning Model can improve student learning outcomes and the average value of students 64.63 in the first cycle to 88.01 in the second cycle. Increased student mastery learning in the first cycle is 14 students or 46.7% increased in the second cycle to 26 students or 86.7%. Thus the completeness of student learning outcomes has reached more than ≥ 70.00. Based on the results of this study it is expected that teachers can be used to add models in learning so as to improve the ability of students in learning.